Pianists on Playing: Interviews with Twelve Concert Pianists - Noyle, Linda J., (Rowman & Littlefield Publishers, 2000)
Twelve internationally-known keyboard artists entertainingly discuss their daily lives of practicing and performing in informative interviews, including reflections on learning new music, reviving repertoire, performing, controlling nerves, recording sessions, playing with ensemble groups, touring, playing in competitions, and the future of the piano. The pianists interviewed include: Vladimir Ashkenazy, Jorge Bolet, John Browning, Bella Davidovich, Misha Dichter, Janina Fialkowska, Rudolf Firkusny, Leon Fleisher, Andre-Michel Schub, Abbey Simon, Ralph Votapek, and Andre Watts.